Comparative risk of high-risk neoplasia after polypectomy among individuals aged below 50 years versus 50 years and older - Chen, Yufeng; Aponte, Jean Padilla; Wang, Kai; Du, Mengxi; Lu, Yujia; Polychronidis, Georgios; Song, Mingyang (Gut, 2026)
Background Limited evidence supports colonoscopy surveillance practices among individuals aged <50 years. - Objective To compare the risk of polyp recurrence and colorectal cancer (CRC) among young and old adults after polypectomy. - Design We prospectively examined the risk of metachronous high-risk neoplasia, including high-risk adenoma, high-risk serrated polyp (SP) and CRC, according to index colonoscopy findings among individuals aged <50 years and ≥50 years who had received ≥1 follow-up colonoscopy in the Mass General Brigham Colonoscopy Cohort (2007-2023). We used a multivariable-adjusted Cox proportional hazards model to calculate HRs. - Results We identified 37 576 adults without polyps, 26 693 with adenomas and 15 425 with SPs (including 8303 with synchronous adenomas and SPs). Among these 10 977 (29.2%), 3385 (12.7%) and 2659 (17.2%) were diagnosed before age 50 years, respectively. The associations between index polyp findings and subsequent risk of high-risk neoplasia were stronger for age <50 years than ≥50 years; however, such differences disappeared (Pheterogeneity>0.05) once the analysis was restricted to index colonoscopy for screening purposes only. Among screened individuals, in both age groups, the association was particularly strong for individuals with index high-risk lesions and peaked at 3 years after polypectomy, with HRs (95% CI) of 4.60 (3.63 to 5.84) and 5.59 (3.89 to 8.03) for young adults with index high-risk adenoma and high-risk SPs, respectively. - Conclusion Patients undergoing polypectomy at a screening colonoscopy below age 50 years exhibited a similarly increased risk of metachronous neoplasia as those aged ≥50 years, suggesting that current surveillance guidelines developed in old adults may apply to young adults.